Hedonic Pricing of Rice Attributes, Market Sorting, and Gains from Quality Improvement in the Beninese Market - Ndindeng, S.A.; Twine, Edgar E.; Mujawamariya, Gaudiose; Fiamohe, R.; Futakuchi, K. (Cambridge University Press, 2021)
Latent class analysis is applied to a hedonic price model to examine the presence of heterogeneity in consumer valuation of quality attributes in the Beninese rice market. Three classes of consumers are found in proportions of 5, 56, and 39 percent. We employ a partial equilibrium model and find modest gains in consumer surplus from an increase in head rice and reduction in chalkiness. The results provide evidence of market sorting, which should be taken into consideration in upgrading rice value chains. Also, it is important to assess potential gains from quality improvement to determine priorities for research and development.